Pembelajaran PAI dengan Menggunakan Media Google Classroom pada Masa Pandemi di Sekolah Menengah Atas - Habibullah, Romadlon; Fahrurozi, Fahrurozi; Putri, Rahayu Lestari (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study describes PAI learning through Google Classroom media during the Covid-19 pandemic at SMAN 4 Bojonegoro. This research is descriptive and qualitative. The population and sample are students of class X SMAN 4 Bojonegoro. Research data was obtained through interviews, observation, and documentation. The results showed that the implementation of PAI learning in class X SMAN 4 Bojonegoro during the pandemic season was by using Google Classroom media. The steps taken include; planning, implementation, organization, and evaluation of learning. The supporting factors for learning are; Google Classroom is learning media workshops for teachers and students, a strong network and internet, students having smartphones, and enthusiastic parents. While the inhibiting factors for learning are; the existence of a wrong internet network due to natural conditions, resulting in students' concentration being easily disturbed, and the application of blended learning being less than optimal.